The Effect of Firm Size, Liquidity, and Leverage on Going Concern Audit Opinion with Firm Value as a Consequent Variable - Rezeqi Dewi Ratna Swari; Ina Indriana; Mazda Eko Sri Tjahjono (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to determine the effect of firm size, liquidity, and leverage on going concern opinion with firm value as a consequent variable. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling method used is purposive sampling. The analysis technique used is logistic regression and simple regression. The results of this study indicate that firm size has no significant effect on going-concern audit opinion, liquidity and profitability have a significant effect on going-concern audit opinion, and going-concern audit opinion has no significant effect on firm value.